Direct PCR using Spodoptera frugiperda eggs as template - Loto, Flavia del Valle (2008)
Introduction: PCR is widely employed in a variety of experimental applications such as studies of Spodoptera frugiperda (Sf), an important pest in America. Objective: To optimize direct PCR technique using Sf samples. Material and methods: PCR reactions were performed in 25 μL containing: 21.4 μl sterile water, 0.1 μl of each oligonucleotide primers (JM76 and JM77), 5 μl 5X Taq buffer and 0.2 μl Taq DNA polymerase. One, two or three eggs were added to the reaction mixture. Negative and positive controls were performed with distilled water and purified DNA, respectively. Amplification was performed with the following program: An initial denaturation step at 97ºC for 5 min and then 35 cycles of the following: 1 min at 94ºC, 1 min at 58ºC, 2 min at 72ºC, and a final extension at 72ºC 2 min. Results and Discussion: Samples with 2 eggs were amplified with the same quality as samples amplified with purified DNA. Only one of three amplifications assays was positive in samples with one egg. Samples with 3 eggs were not amplified, probably due to excessive DNA or PCR inhibitors. The method is simple, fast and cost saving. This work was supported by grants PICTO-UNT 761 and PIP 6062 (CONICET).